An Ultrafast One-Step Quantitative Reverse Transcription–Polymerase Chain Reaction Assay for Detection of SARS-CoV-2 - Milosevic, Jadranka; Lu, Mengrou; Greene, Wallace; He, Hong-Zhang; Zheng, Si-Yang (Frontiers in Microbiology, 2021)
We developed an ultrafast one-step RT-qPCR assay for SARS-CoV-2 detection, which can be completed in only 30 minutes on benchtop Bio-Rad CFX96. The assay significantly reduces the running time of conventional RT-qPCR: reduced RT step from 10 to 1 minutes, and reduced PCR cycle of denaturation from 10 to 1 second and extension from 30 to 1 second. A cohort of 60 nasopharyngeal swab samples testing showed that the assay had a clinical sensitivity of 100% and a clinical specificity of 100%.